Investment Liberalization in the ASEAN Economic Community Vietnam’s Participation, Opportunities and Challenges - Phương, Nguyễn Thị Minh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2014)
Abstract: Investment liberalization plays an important role in building a single market and production base in the ASEAN Economic Community (AEC). The paper examines Vietnam’s participation in the AEC from the perspective of investment liberalization through analysis of: (i)   Vietnam’s commitments and her implementation of commitments under the ASEAN Comprehensive Investment Agreement (ACIA); (ii) the current situation of foreign direct investment (FDI) in ASEAN and Vietnam; and (iii) opportunities and challenges for Vietnam from AEC’s liberalization of investment. Keywords: AEC, ACIA, FDI, Vietnam.